2022
DOI: 10.3389/fpsyg.2022.885278
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Positive Mental Health and Depression in Africa: A Variable-Based and Person-Centred Analysis of the Dual-Continua Model

Abstract: The dual-continua model of mental health provides a contemporary framework for conceptualising and operationalising mental health. According to this model, mental health is distinct from but related to mental illness, and not the opposite or merely the absence of psychopathology symptoms. To examine the validity of the dual-continua model, previous studies have either applied variable-based analysis such as confirmatory factor analysis (CFA), or used predetermined cut-off points for subgroup division. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
3
7
0
Order By: Relevance
“…Instead, we identified a partially symptomatic and content profile, with only moderate mental well-being and moderate ED symptomatology. While symptomatic but content profiles have been identified in previous research using different methods to derive mental health profiles (Keyes, 2005;Renshaw & Cohen, 2014), other LPA dual continua studies have found results similar to the present study (Khumalo et al, 2022;Moore et al, 2019aMoore et al, , 2019bThayer et al, 2021). For example, in a study of African and South African university students, Khumalo et al (2022) used LPA and found a profile of students who had moderate wellbeing and moderate depressive symptoms (i.e., partially symptomatic and content), and no profile where students endorsed high well-being and high depressive symptoms (i.e., symptomatic but content).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Instead, we identified a partially symptomatic and content profile, with only moderate mental well-being and moderate ED symptomatology. While symptomatic but content profiles have been identified in previous research using different methods to derive mental health profiles (Keyes, 2005;Renshaw & Cohen, 2014), other LPA dual continua studies have found results similar to the present study (Khumalo et al, 2022;Moore et al, 2019aMoore et al, , 2019bThayer et al, 2021). For example, in a study of African and South African university students, Khumalo et al (2022) used LPA and found a profile of students who had moderate wellbeing and moderate depressive symptoms (i.e., partially symptomatic and content), and no profile where students endorsed high well-being and high depressive symptoms (i.e., symptomatic but content).…”
Section: Discussionsupporting
confidence: 85%
“…While symptomatic but content profiles have been identified in previous research using different methods to derive mental health profiles (Keyes, 2005;Renshaw & Cohen, 2014), other LPA dual continua studies have found results similar to the present study (Khumalo et al, 2022;Moore et al, 2019aMoore et al, , 2019bThayer et al, 2021). For example, in a study of African and South African university students, Khumalo et al (2022) used LPA and found a profile of students who had moderate wellbeing and moderate depressive symptoms (i.e., partially symptomatic and content), and no profile where students endorsed high well-being and high depressive symptoms (i.e., symptomatic but content). An alternative interpretation is that these individuals could be positioned on the mid-point of the unidimensional model, with moderate levels of mental well-being and mental illness that places them towards the centre of this continuum.…”
Section: Discussionsupporting
confidence: 85%
“…With (a), for example, Iasiello et al (2022) conducted a meta‐analysis of 46 studies that used the Mental Health Continuum—Short Form, and found the scale provides a robust measure of general mental well‐being, tapping into emotional, social, and psychological aspects of well‐being in both general and clinical populations. We are also seeing inroads using a person‐centered approach, some of which also combine construct validation, as per Khumalo et al's (2022) analysis above. However, the matrices have the potential to further enhance this line of research.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 97%
“…This recognition is reflected in certain work on the dual-continua model which, rather than the standard four categories discussed above, has explored more granular profiles of mental illness and health. Khumalo et al (2022), for example, used confirmatory factor analysis and latent class analysis to test the model in relation to the Mental Health Continuum-Short Form and Patient Health Questionnaire-9, and developed a profile featuring 23 different indicators, 9 pertaining to illness (loss of interest, depressed mood, sleep disturbance, fatigue, appetite change, self-reproach, concentration problems, psychomotor problems, and thoughts of suicide), and 14 to health (happiness, interest in life, satisfaction, social contribution, social integration, social acceptance, social coherence, self-acceptance, environmental mastery, positive relations with others, personal growth, autonomy and purpose in life). While in certain contexts the greater simplicity of the broad four-category classification may be preferable, a more granular approach inevitably provides a more detailed assessment of a person's mental illness and health.…”
Section: The Mih Matrixmentioning
confidence: 99%
“…The third component is social well-being, which is positive social functioning. The continuum model of mental health has been supported by considerable evidence base from across cultures (Khumalo et al, 2022;Żemojtel-Piotrowska et al, 2018;Zhang et al, 2021).…”
Section: Languishing In Popular Media and The Two Continua Modelmentioning
confidence: 99%